e-Traumatization: Acquired Trauma through Media Platforms - Andrie Jann V Akilith; Kathleen P Cristobal; Miguel G Madamba Jr (RSF Press, 2025)
Using Foa and Kozak’s fear network model, this study explored the lived experiences of individuals exposed to disturbing content across various media platforms. Through an Interpretative Phenomenological Approach (IPA), the study identified three key themes: Personal Distress, reflecting emotional struggles and intrusive thoughts akin to traditional PTSD symptoms; Digital Hypervigilance, mirroring heightened vigilance and avoidance behaviors; and Adaptive Mechanisms, highlighting coping strategies developed to manage distress. This study raises public awareness about the psychological impact of engaging with disturbing media content and deepens understanding of how media-acquired trauma parallels traditional traumatic stress. Recommendations include psychotherapy tailored for e-traumatization, stricter content moderation on media platforms, accessible helplines on social media, and public awareness campaigns to mitigate the effects of disturbing media content.